A Case Study of Nematode Communities’ Dynamics along Successional Paths in the Reclaimed Landfill - George P. Stamou (Diversity, 2020)
We assessed the abundance and composition of nematode communities in soil under herbaceous vegetation in reclaimed landfill sites at different ages after closure (3, 10 and 14 years) compared to those in neighboring semi-natural grazed grasslands (reference sites). We further applied network analysis based on the co-occurrence patterns of nematodes. Nematode abundance decreased between 3 and10 years of regeneration, but significantly increased from 10 to 14 years of regeneration. The number and identity of genera were comparable along the succession; however, there were dissimilarities in community composition during early- and mid-succession. The diversity, community composition and abundance at the sites after 14 years of regeneration converged with those at the reference sites. Moreover, changes during succession were not accompanied by the maturation of the soil food web, as demonstrated by Enrichment and Channel indices. In all the networks, centrality and modularity metrics differed significantly from those for random networks, whereas cohesion metrics showed no difference. All the networks exhibited Small-worldness indices higher than one, demonstrating that the networks of the interactions among genera at all the sites shared features that matched both random and non-random networks. The succession trajectory in reclaimed landfills was represented by a sequence of changes that differed in relation to the variable under consideration; network parameters tended to converge with those of a relatively resistant reference community, while the Enrichment and Channel indices did not. Additionally, the succession trajectory was not linear or steady; only the Channel index and Worldness index showed linear responses to succession time. However, across all the successional stages, the resource status remained basal or degraded while the nematode communities had an enhanced ability to cope with sudden changes.